Особливості хірургічного лікування пацієнтів із зобом великих розмірів - Павловський, М. П.; Коломійцев, В. І.; Сироїд, О. М. (Clinical Endocrinology and Endocrine Surgery, 2009)
The pecualirities of surgical treatment of 194 patients with large goiter (mass more than 100 g) in the age of 34-80 (average age 61.9±9.1) years are analysed. Nodal nontoxic goiter diagnosed in 164 (84.5 %) cases, toxic goiter — in 19 (9.8 %), Hashimoto’s thyroiditis — in 11 (5.7 %) cases. The tracheal intubation was difficult at 98 (50.5 %) patients. We had the necessity to cut up the short muscles of neck for good surgical access to thyroid gland in 33.5 % patients with large goiter. In all patients it was not possible to visualizate the recurrent laryngeal nerve and parathyroid glands before end of mobilization of thyroid due to large dimension of goiter. Thyroidectomy were mainly performed in this patients. However, the number of postoperative complications essentially did not increase.